2014
DOI: 10.1021/om5002759
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity Studies on an Intramolecularly Coordinated Organotin(IV) Carbonate

Abstract: The reactivity of the intramolecularly coordinated organotin-(IV) carbonate L(Ph)Sn(CO 3 ) (1), where L stands for an N,C,N-chelating ligand, 2,6-(Me 2 NCH 2 ) 2 C 6 H 3 , was studied. The treatment of 1 with ferrocene-based carboxylic acids RCOOH afforded the organotin(IV) dicarboxylates LPhSn(O 2 CR) 2 , where R is ferrocenyl (2), 2-ferrocenylethyl (3), and [(1E)-2-ferrocenyl]ethenyl (4). Surprisingly, compounds 2−4 are sensitive to moisture and easily hydrolyze with condensation into the corresponding hexam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 78 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…The S 1B -S 2B bond length is 2.050(2) Å, which is a typical value for a S-S single bond, and comparable to H 2 S 2 with a S-S bond length of 2.055 Å. 44 The S⋯S distance between the two units is 3.491 Å, excluding the possibility of a S 4 2− unit.…”
Section: Elemental Sulfurmentioning
confidence: 87%
See 1 more Smart Citation
“…The S 1B -S 2B bond length is 2.050(2) Å, which is a typical value for a S-S single bond, and comparable to H 2 S 2 with a S-S bond length of 2.055 Å. 44 The S⋯S distance between the two units is 3.491 Å, excluding the possibility of a S 4 2− unit.…”
Section: Elemental Sulfurmentioning
confidence: 87%
“…Boroxines are rigid bidentate ligands which have drawn attention recently, mostly by forming complexes of main group elements, e.g. for Al; [38][39][40] Sn, Sb and Bi; [41][42][43][44][45][46][47] but also for transition metals such as Mn, 48 Au 37,49 and Pt. 50 Single crystals of 5 m and 6 m were obtained by slow diffusion of hexanes into a benzene solution.…”
Section: Triphenylphosphine Oxidementioning
confidence: 99%
“…There are also a limited number of molecular compounds with eight-membered rings of the type Si 2 B 2 O 4 . We recently entered this field demonstrating that series of stiba-, bisma-, and stannaboroxines with central six-membered MB 2 O 3 core (where M = Sb, Bi, or Sn) are quite easily accessible via simple condensation reaction of parent boronic acids and proper organometallic precursors, namely, oxides (ArSbO) 2 ( 1 ) and (ArBiO) 2 ( 2 ) or organotin­(IV) carbonate Ar­(Ph)­Sn­(CO 3 ) ( 3 ) [where Ar is an abbreviation for the N,C,N-chelating ligand C 6 H 3 -2,6-(CH 2 NMe 2 ) 2 ] . It has also been shown that analogous heteroboroxines could be obtained by a conversion between boroxine rings R 3 B 3 O 3 (R = Me or MeO) and 1 – 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Contributing to widen phosphonate family compounds, the Dakar group has already reported the spectroscopic (Infrared, Mössbauer and NMR) studies of some RPO 3 (SnPh 3 ) 2 (R = H or CH 3 ) (Diop et al, 1999), the crystal characterization of dibutylammonium bis(hydrogen methylphosphonato-κO)triphenylstannate(IV) (Diop et al, 2012a) as well as numerous phenylphosphonato triphenyltin(IV) crystalline structures which, through hydrogen bonding interactions, exhibit various structures that give rise to supramolecular diverse topologies (Diop et al, 2013a(Diop et al, , 2012b(Diop et al, , 2011a(Diop et al, , 2011b. To the best of our knowledge (CSD version 5.40), very few, only three tin(IV) methylphosphonate and five tin(IV) hydrogenphosphonate containing crystalline compoundsare known (Diop et al, 2012a;Ribot et al, 2001;Adair et al, 1998;Chandrasekharet al, 2003Chandrasekharet al, , 2005Mairychova et al, 2014 (Mairychova et al, 2014) or an hexameric cage structure in a double O-capped cluster with tri-O-coordinating ligands (Chandrasekharet al, 2003(Chandrasekharet al, , 2005. Thus,continuing to focus in phosphonato organotin(IV) family compounds, we investigated in this work, in organic solvents,the interactions between a salt of methylphosphonic acid, CH 3 PO(OH) 2 andhexamethylene tetraamine (L) and, trimethyltin(IV) chloride in one hand and, phosphorous acid, HPO(OH) 2…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%